Answer:From first time to second time
1:49
From second time to first time
-1:49
From first time to second time over midnight
25:49
From second time to first time over midnight
22:11
Step-by-step explanation:
Answer:
Show the whole photo and you will maybe get help
Step-by-step explanation:
Notice that half of the coefficient of x is (1/2)(-4), or -2.
Then x^2 - 4x becomes
x^2 - 4x + 4 - 4 = 0, or (x -2)^2 = 4. Then x = -2 plus or minus 2, and the two roots are 0 and -4.
Thus, add 4 to both sides to obtain x^2 - 4x + 4 = 4.
Answer: (-3,-2)
Step-by-step explanation: